The primitive - Amidon, Stephen 1959- (Ecco Press, 1995)
In North Carolina, a woman escapes from hospital after a car accident, arriving in the office of the real estate agent who caused it, asking his help without explaining why. He is so intrigued he offers her one of the agency's houses and begins an affair behind his wife's back, unaware of what he is getting into.
Keywords: Frau; Women artists -- Fiction; Women -- North Carolina -- Fiction; North Carolina -- Fiction; Romantic suspense fiction